Thermal conductivity of major rock types in western and central Anatolia regions, Turkey - ERKAN, KAMİL (OXFORD UNIV PRESS, 2017)
Thermal conductivity is a key parameter in heat flow and geothermal investigations as it controls the temperature distribution within the Earth. Turkey has a significant geothermal potential yet rock thermal conductivity studies have been very limited. Here, we report new thermal conductivity values collected from 240 rock samples in western and central Anatolia regions. The data were initially classified according to lithologic descriptions; then mean thermal conductivities were determined after applying corrections from dry to saturated conditions, if necessary. The major rock types encountered in these regions are igneous metamorphic, and sedimentary rocks. Limestone is the most common lithological unit encountered both in western and central Anatolia regions. The limestones in western Anatolia show a higher mean thermal conductivity than the limestones in central Anatolia. Dolomitization has a significant effect on the thermal conductivity of limestones. Neritic limestones show a higher mean thermal conductivity compared to lacustrine limestones. The results of this study reveal large contrasts in thermal conductivity values among different rock types that can have major implications for future heat flow and geothermal modeling studies in these regions.
Keywords: thermal conductivity; western Anatolia; central Anatolia; geothermal; heat flow; HIGH-PRESSURE METAMORPHISM; SOUTHERN MENDERES MASSIF; HEAT-FLOW; TECTONIC EVOLUTION; CORE COMPLEX; SUBDUCTION; EXTENSION; EXHUMATION; BASIN; PART